2021
DOI: 10.3174/ajnr.a7138
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI Shows Altered Deactivation and a Corresponding Decrease in Functional Connectivity of the Default Mode Network in Patients with Gliomas

Abstract: BACKGROUND AND PURPOSE:The default mode network normally decreases in activity during externally directed tasks. Although default mode network connectivity is disrupted in numerous brain pathologies, default mode network deactivation has not been studied in patients with brain tumors. We investigated default mode network deactivation with language task-based fMRI by measuring the anticorrelation of a critical default mode network node, the posterior cingulate cortex, in patients with gliomas and controls; furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Regarding the default mode network (DMN), the results reported in the literature are unable to provide a clear and unequivocal picture of the alterations. In fact, from recent studies, both decrement [31] and increment of the overall FC within such network [32], and with the other brain networks [34], were detected. However, it is to note that even where a global increase was found, local negative alterations in the posterior cingulate cortex (PCC) and the precuneus were observed [32].…”
Section: Default Mode Networkmentioning
confidence: 82%
See 2 more Smart Citations
“…Regarding the default mode network (DMN), the results reported in the literature are unable to provide a clear and unequivocal picture of the alterations. In fact, from recent studies, both decrement [31] and increment of the overall FC within such network [32], and with the other brain networks [34], were detected. However, it is to note that even where a global increase was found, local negative alterations in the posterior cingulate cortex (PCC) and the precuneus were observed [32].…”
Section: Default Mode Networkmentioning
confidence: 82%
“…In particular, the first applications of deep learning methods have been showing that such an approach can achieve excellent outcomes for the specific purpose of reconstructing tb-fMRI-like networks, starting from the rs-fMRI data. Nevertheless, it is also significant to note that ICA is already widely acknowledged, so much so that it is also used to isolate the functional networks in studies that do not focus on their identification but rather aim at characterizing their properties in terms of FC [29][30][31][32].…”
Section: Language Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have reported a higher mean connectivity ( Otten et al, 2012 ) and brain-wide disrupted networks associated with tumor-related remodeling of the neurovasculature ( Hadjiabadi et al, 2018 ). In particular, several research groups measured the DMN in glioma by rs-fMRI and observed the increased integration of DMN in hippocampal areas, but the decreased integration in prefrontal and posterior cingulate cortex regions, and a trend of decreasing global connectivity with a higher WHO grade ( Esposito et al, 2012 ; Harris et al, 2014 ; Maniar et al, 2021 ). The decreased DMN integration and deactivation may lead to cognitive decline of patients.…”
Section: Functional Connectome and The Alternations In Gliomasmentioning
confidence: 99%
“…Then we proofread the scanning time point of each layer image, and the head motion correction was used to exclude subjects with excessive head movement. Next, we used the Echo-Planer Imaging (EPI) template of the Montreal Neurologic Institute (MNI) space to standardize the image registration to 3 mm × 3 mm × 3 mm (Brandman et al, 2021;Fan et al, 2021;Peng et al, 2021), and 1 https://www.fil.ion.ucl.ac.uk/spm/software/spm12 finally the Gaussian kernel with a half-height full-width value of 6 mm was used for spatial smoothing to reduce spatial noise (Maniar et al, 2021;van Buuren et al, 2021).…”
Section: Data Preprocessingmentioning
confidence: 99%